2007
DOI: 10.1002/mds.21907
|View full text |Cite
|
Sign up to set email alerts
|

Excessive dopamine neuron loss in progressive supranuclear palsy

Abstract: Progressive supranuclear palsy (PSP) and Parkinson's disease (PD) differ in their response to dopaminergic replacement therapies, despite having a similar degree of neuronal degeneration in the dopaminergic substantia nigra. We observed more widespread dopamine neuron loss in the extranigral A10 midbrain cell groups in PSP compared with PD. These cell groups innervate subcortical and cortical regions and may be required for adequate response to levodopa therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 7 publications
2
16
0
Order By: Relevance
“…These results are supported by a pathology study that found a more widespread loss of dopamine neurons in PSP than in PD (30). In terms of the ventrodorsal gradient, we also found a more profound DAT loss in the AC than in the VS; this feature provided the best diagnostic value for differentiating the PSP group from other groups.…”
Section: Discussionsupporting
confidence: 87%
“…These results are supported by a pathology study that found a more widespread loss of dopamine neurons in PSP than in PD (30). In terms of the ventrodorsal gradient, we also found a more profound DAT loss in the AC than in the VS; this feature provided the best diagnostic value for differentiating the PSP group from other groups.…”
Section: Discussionsupporting
confidence: 87%
“…Our work therefore directly demonstrates that iPSCs, especially isogenic iPSCs, are a powerful tool not only for disease modeling but also for studies of disease mechanisms. Interestingly, dopaminergic neurons are especially vulnerable to TAU-A152T-induced neurotoxicity, which is in line with the observation that tauopathy in PSP is associated with excessive dopaminergic neuron loss (Murphy et al., 2008). The underlying mechanism remains to be determined.…”
Section: Discussionsupporting
confidence: 85%
“…Therefore, although pathology in PSP‐P was not distinctive, the restricted, mild tau pathology in PSP‐P supported its clinical distinction from PSP‐RS . For instance, the excessive loss of dopaminergic neurons in SN and extranigral midbrain cell groups in PSP‐RS may compromise any therapeutic response to l ‐dopa, and contribute to behavioral and motor symptoms characteristic for PSP. Less severe pathology in the extranigral midbrain in PSP‐P may be associated with moderate l ‐dopa responsiveness in this PSP variant.…”
Section: Discussionmentioning
confidence: 97%